Analisa Deskriptif Keterlambatan Pekerjaan Proyek Konstruksi Eto Tower Dili, Timor-Leste - I Komang Agus Ariana; Dewa Ayu Putu Adhiya Garini Putri; Messias Da Costa Boavida (Jurnal Ilmiah Telsinas, 2022)
In general, every implementation of a construction project there is always a work delay. The delay in this work has an impact on the implementation of the Eto Tower construction project in Dili, Timor-Leste which will be carried out in January 2020 to January 2021, but has been delayed. Thus, the purpose of this study is to describe what causes delays in the Eto Tower construction project. Descriptive statistical analysis was used in this study. Where the number of samples is 33 employees which is the entire population. The results of this study indicate that the main causes that affect the delay in the Eto Tower construction project are environmental factors with a mean value of 27.24, lack of materials and materials with a mean value of 26.85 and the cause of equipment with a mean value of 26.67. Support from the local community in the project is needed.